i-CARE2U: easy-to-use application software to enhance knowledge and awareness of Malaysians towards the rights of persons with disabilities / Muhammad Fikri Othman ... [et al.] - Othman, Muhammad Fikri; Rahmat, Nur Ezan; Abdul Aziz, Norazlina; Abdul Hak, Nora; Kamarudin, Diyana (2021)
Persons with disabilities (PwDs) and children with disabilities in Malaysia have been treated negatively by Malaysian citizens. This negative treatment can be seen in terms of social interaction, education and employment. About 48% of Malaysian citizens avoid having interaction with them due to negative perceptions towards disability. Children with disabilities are not given equal educational rights as other normal children to access education due to some requirements imposed by the Ministry of Education and school administrators. Besides, employers are reluctant to employ PwDs due to the negative perception that they are less productive than other employees. Because of the negative perceptions and attitudes towards Pwds and children with disabilities, they cannot enjoy their life as other normal people. This application is developed to assist Malaysian citizens to understand the status and nature of the disability, the rights that the law has conferred toward PwDs and children with disabilities and laws relating to disabled people. Therefore, Malaysian citizens can improve their knowledge on disabilities. Thus, the negative perceptions and attitudes towards disabled people can be eliminated through this application. There are a few categories of disabled people. Under the Department of Social Welfare, seven categories of PwDs can be considered for registration. In Malaysia, there are a few rights that have been conferred on the PwDs and children with disabilities, such as the right to access public facilities, amenities, services and buildings, right to the access and use of public transport facilities, right to access equal education opportunities, and right to access employment as provided under the Persons with Disabilities Act 2008. This application is easy to use and user-friendly, efficient and informative to be used by all Malaysian citizens.